Juvenile xanthogranuloma regresses more rapidly than hemangioma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
A 2-month-old little girl was first observed for an angiomatous lesion of the left buttock, present since birth as a flat red patch, which became progressively more raised. We diagnosed hemangioma and advised the mother to avoid the disposable diaper during the waking period aimed at decreasing the risk of ulceration.There was also on the same buttock from the first month of life an about 1 cm in size, pink, hard and tense nodule leading to the clinical suspicion of fibrous histiocytoma (Fig. 1). In the following months the nodule became progressively yellower (Fig. 2, 3) leading at the age of 5 months to diagnose juvenile xanthogranuloma. We saw again the child at 9 months of age: hemangioma was essentially unchanged while juvenile xanthogranuloma had lost its yellow color and had clearly regressed (Fig. 4).